Strict Action Against Land Mafia - Darma, Mospa (Review: Journal of Multidisciplinary in Social Sciences, 2025)
Law enforcement is a concrete manifestation of a state based on the rule of law. Law can only be beneficial when it is enforced, and law enforcement is carried out by law enforcers. Because law enforcers are part of society, they must be able to cooperate with the law. For the public to assess good law enforcement, legal regulations are needed to provide systematic guidance. This research uses a normative juridical research method to collect data related to this research. This research took place within the jurisdiction of the North Sumatra Regional Police, dealing with the handling of land mafia acts. Land mafia are individuals or groups who violate land laws by exploiting loopholes to violate land ownership, whether SHM, HGB, HGU, or Sub-district Head's Decree. In practice, they involve the government, including village heads, notaries, and the National Land Agency (BPN). Legal smuggling involves various legal acts, including falsifying data and mechanisms that violate the law, based on false rights. The techniques they employ obscure the origin and process of issuing SHMs on land owned by the actual owner, who already has official land rights. Efforts to eradicate land mafias, carried out by law enforcement officials, are still weak and detrimental to the vulnerable, especially those in need. They often exploit the weaknesses of government officials, notaries, and ultimately the National Land Agency (BPN), which is trapped by the mafia's submitted documents. The eradication of land mafias must be carried out systematically, with the threat of strict penalties and clear enforcement of penalties for officials who collaborate in weakening the law and even evading the law, carried out in a clear and transparent manner